Understanding genomic diversity in Pseudomonas syringae throughout the forest and on the trees. Issue 2 (21st June 2018) - Baltrus, David A.; Orth, Kelly N.
Abstract : This article is a Commentary onHulin et al., 219 : 672–696 .